Sulfate reduction at low pH to remediate acid mine drainage - Sánchez-Andrea, Irene (2014)
Industrial activities and the natural oxidation of metallic sulfide-ores produce sulfate-rich waters with low pH and high heavy metals content, generally termed acid mine drainage (AMD). This is of great environmental concern as some heavy metals are highly toxic. Within a number of possibilities, biological treatment applying sulfate-reducing bacteria (SRB) is an attractive option to treat AMD and to recover metals. The process produces alkalinity, neutralizing the AMD simultaneously. The sulfide that is produced reacts with the metal in solution and precipitates them as metal sulfides. Here, important factors for biotechnological application of SRB such as the inocula, the pH of the process, the substrates and the reactor design are discussed. Microbial communities of sulfidogenic reactors treating AMD which comprise fermentative-, acetogenic- and SRB as well as methanogenic archaea are reviewed.